The Term Structure as a Predictor of Real Economic Activity. - Estrella, Arturo; Hardouvelis, Gikas A (Journal of Finance, 1991)
A positive slope of the yield curve is associated with a future increase in real economic activity: consumption (nondurables plus services), consumer durables, and investment. It has extra predictive power over the index of leading indicators, real short-term interest rates, lagged growth in economic activity, and lagged rates of inflation. It outperforms survey forecasts, both in-sample and out-of-sample. Historically, the information in the slope reflected, inter alia, factors that were independent of monetary policy and, thus, the slope could have provided useful information both to private investors and to policymakers.